Pengaruh Berbagai Macam Pendinginan dan Pengemasan Terhadap Umur Simpan Jagung Manis (Zea mays saccharata) - Rustiningsih Rustiningsih; Nafi Ananda Utama; Innaka Ageng Rineksane (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
This  research was aimed to study  the influence  of   kinds of cooling and packing  on the storage life of sweetcorn in order to obtain the simple postharvest  technology and easy to practice.  The research was done during the February - March of 2005 in the Research Laboratory of Agriculture Faculty, Muhammadiyah  University of Yogyakarta.  The reducing sugar analysis was done in the  Agriculture Technology Faculty of Gadjah Mada University. The laboratory  experiment  was arranged  ini 2 x 3 factorial  completely  randomized design with three replications.  The cooling first factor  was refrigerated in refrigerator to be compared  to the hydro-cooling.  Meanwhile,  the polypropilene and polyethylene  packaging were tested and compared to the unpackaged one. The flavor; reducing sugar, water content, percentage  of nonconsumable  part of sweetcorn,   fresh  weight  of ears,  and organoleptic properties  were observed. The result showed  that there was no significantly   interaction between cooling and packaging on  the  storage life  and  quality  of  sweet corn. The  cooling treatment was significantly influenced the starch and reducing sugar level  as well as the packaging treatment. Refrigeration   storage could significantly keep   the  level   of reducing  sugar  to remain higher than the hydro-cooling, this treatment  was also   decreased the starch  content, decreased the proportion  of unconsumable  part,  and maintained   the flavor. The  polyethylene    packaging significantly keep the level  of reducing  sugar to remain higher and relatively maintained the flavor   than  the polypropilene packaging or  unpackaged, but  decreased  the portion  of unconsumable  part.